Az erdélyi orgonatáj fotográfusa – Buzogány Dezső orgonaképei (Mozaikok, nem csak zenéről) - DÁVID, István (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
The photographer of the Transylvanian Organ Landscape – Organ Photos made by Dezső Buzogány (Mosaics, not only from Music). To take a photo inventory of the Transylvanian organs is not only a musical or artistic challenge. It is more important to have friendly relations between the organist – like researcher of the instrument – and the photographer of these marvellous artistic facades. In this article there are presented some pleasant mosaics, memories, remembrances from the past, about the beginning and getting stronger of such a professional collaboration with new and new experiences. In the book Organ-Monuments in Transylvania written by the organist István Dávid, there are more than 30 photos in the Picture Index, each made by prof. Dezső Buzogány. The number of offered photos was much more, some of them with historic value, as the situation changed ever since. This article included 6 Buzogány-photos from the Transylvanian Organ Landscape, made years ago, by the young pastor of Selye and Ádámos Reformed Congregations. And you will find here 6 organs, with a short history of each other as: Segesvár (Sighişoara), Ádámos (Adămuş), Agyagfalva (Lutiţa), Medgyes (Mediaş), Siménfalva (Şimoneşti), Kolozsvár (Cluj).